Estimates for sums of independent random values in symmetrical spaces - Braverman , M. Sh. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
For a class of symmetric spaces of random variables, the equivalence of fulfilment of the upper bounds of the same type for collections of disjunctive and independent random variables is established.